Renal cell carcinoma: evolving approaches to advanced non-clear cell carcinoma - Daniel Y.C. Heng; Ronald M. Bukowski (Frontiers Media S.A., 2011)
The treatment of metastatic renal cell carcinoma (RCC) has changed dramatically with the introduction of targeted therapies including sunitinib, sorafenib, and temsirolimus. Because patients with conventional clear cell histology account for 75- 80% of all patients with RCC, there has been little accumulated evidence on the treatment of patients with non-clear cell histologies. Most clinical trials have excluded them from enrolment, except for randomized studies investigating temsirolimus. Many retrospective studies on the use of all three of these targeted therapies in patients with non-clear cell histology have demonstrated response rates ranging from 3.7%-16%. Although response rates may not be as high compared to patients with clear cell histologies, targeted therapy does provide a clinically meaningful response.